Predicting online banking fraud using adaptive neuro-fuzzy inference system (ANFIS) - Zammarah, Nuha Abdullah; Shah, Asadullah (IIUM Press, International Islamic University Malaysia, 2017)
Online banking is growing tremendously in recent years. This is attributed to the explosion in internet technologies on both computer and handheld-devices platforms. Unfortunately, the growth of online banking is accompanied by a persistent growth of attacks in the form of phishing and malware. Therefore, ensuring security of personal data during transactions is of utmost concern. Security standards have become more stringent in order to counter the growth rate of online fraud. Multiple defensive security lines have also been proposed to reduce the rate of attacks. Customer and vendor awareness are considered important in the fight against online fraud. Technical solutions such as online bank coders/decoders are further presented as a solution to fraud. Nevertheless, despite all the efforts involved, fraud is still increasing. This relentless growth in online fraud has provoked this work, which seeks to deal with fraud from a different perspective.